The Validity of Science Learning Devices Based on the 7E Learning Cycle Model to Improve Concept Mastery of Junior High School Students - Muliadi Rahman; Agus Ramdani; Jamaluddin Jamaluddin (IKIP Mataram, 2021)
This study aimed to develop a science learning tool based on the 7E learning cycle model that is valid to improve the mastery of concepts and science process skills for Junior high school students. The device development carried out refers to the Research and Development (R & D) development model based on the Thiagarajan 4D development model which includes the design, define, develop and disseminate stages. Based on the results of validation by 3 expert validators, it was obtained that the average value of the validity of the learning learning tools developed included the Syllabus 83.33%, lesson plan 81.48%, student worksheet 74.17%, Concept Mastery Assessment Instruments 77.78% and science process skills tests 80.00%. Based on the results of validation by 3 validators, In conclusion, the science learning device based on the 7E learning model developed is valid for use in learning.